2006
DOI: 10.1029/2006gl027642
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for rainfall‐triggered earthquake activity

Abstract: [1] Fluids are known to be of major importance for the earthquake generation because pore pressure variations alter the strength of faults. Thus they can initiate earthquakes if the crust is close enough to its critical state. Based on the observations of the isolated seismicity below the densely monitored Mt. Hochstaufen, SE Germany, we are now able to demonstrate that the crust can be so close-to-failure that even tiny pressure variations associated with precipitation can trigger earthquakes in a few kilomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
173
2
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(207 citation statements)
references
References 26 publications
11
173
2
2
Order By: Relevance
“…For Parkfield, the hydraulic diffusivity calculated based on the average depth of earthquakes (5 km) and an apparent lag time of $5 months is 2 m 2 /s. This value is similar to the value invoked to explain precipitation-induced earthquakes in Bavaria (3.3 ± 0.8 m 2 /s) [Hainzl et al, 2006]. However, it is much higher than that inferred from the water-level response of Parkfield wells to barometric pressure ($10 À4 m 2 /s) [Roeloffs, 1998] or from a pumping test in another active fault (7 ± 1 Á 10 À5 m 2 /s) [Doan et al, 2006].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…For Parkfield, the hydraulic diffusivity calculated based on the average depth of earthquakes (5 km) and an apparent lag time of $5 months is 2 m 2 /s. This value is similar to the value invoked to explain precipitation-induced earthquakes in Bavaria (3.3 ± 0.8 m 2 /s) [Hainzl et al, 2006]. However, it is much higher than that inferred from the water-level response of Parkfield wells to barometric pressure ($10 À4 m 2 /s) [Roeloffs, 1998] or from a pumping test in another active fault (7 ± 1 Á 10 À5 m 2 /s) [Doan et al, 2006].…”
Section: Discussionsupporting
confidence: 79%
“…Pore-pressure diffusion is one possible causal mechanism that has received considerable recent attention [cf. Saar and Manga, 2003;Christiansen et al, 2005;Hainzl et al, 2006]. Hydrologic recharge increases pore pressure and thereby decreases effective stress at depth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, both natural and engineering processes that can increase pore pressures and hence influence seismicity (Wang and Manga 2009). A correlation between precipitation and earthquakes (Jiménez and Garcia-Fernández 2000;Ogasawara et al 2002;Hainzl et al 2006;Kraft et al 2006;Husen et al 2007) supports the idea that pore pressure changes caused by rainfall recharge can influence seismicity. The distinctive signature of earthquakes triggered by pore pressure stress is a spatial migration of swarm epicenters.…”
Section: Rainfall-triggered Seismicitymentioning
confidence: 90%
“…Previously was pointed the role of water on the generation of intraplate seismicity by Costain et al (1987). Hainzl et al (2006) have found the clear evidence that pore pressure changes induced by rainfall are able to trigger earthquake activity even at surficial depth via the mechanism of fluid diffusion. However, Kraft et al (2006) have revealed the two cases of earthquake swarms that follow heavy rainfall events.…”
Section: Rainfall-triggered Seismicitymentioning
confidence: 99%